Association between nutritional profile, breastfeeding outcomes and employment status among malay mothers in Selangor , Malaysia / Wan Amirah Che Hashim…[et al.] - Che Hashim, Wan Amirah; Alias, Nurul Fakhriah; Ab.Ghani, Munirah; Abd Wahab, Nur Izzati (2016)
Observations on women's trend in labour force in Malaysia prior to the research period are increased by the years. This trend can influence on mother's nutritional profiles in term of dietary intake and body composition. Therefore, these factors are determinant for the success of breastfeeding outcome. This study was conducted to investigate association between nutritional profiles and employment status on breastfeeding outcomes among Malay mothers in Selangor. Using a prospective cohort design, employed and unemployed mothers were recruited through convenience sampling from Mothers and Child Health Clinic setting in three districts in Selangor which is Klang, Gombak, Petaling and Shah Alam. The nutritional status of the maternal was assessed using anthropometrical and food frequency questionnaires (FFQ). The anthropometrical data were taken and later were compared with WHO, BMI for Asian. Whereas, the FFQ were analysed and later compared with RNI. This research found that, employed mothers initiate breastfeeding soon after birth but duration of breastfeeding decline over postpartum period. On average, the complementary foods practices were introduced during 6 months among employed and unemployed mothers. While, more than half of nutrients meet the recommended nutrient intake (RNI) 2005 among employed and unemployed Malay mothers. Next, the mean of weight, body mass index (BMI),fat free mass (FFM) and total body fat percentage among employed mothers was high compared to unemployed who practising the same breastfeeding type, EBF. The dietary intake is not a major factor that can influence breastfeeding duration. Overall, although some of result obtained is not statically significance but it is proven that nutritional profile and employment status plays an essential role in determining breastfeeding outcome which may influence infant's health and development in later life.